Predictors of high dose of massed practice following stroke - Sabo Bishir; Abdullahi Auwal; Badaru Umaru Muhammad; Saeys Wim; Truijen Steven (Translational Neuroscience, 2022)
The aim of this study is to determine the factors that affect patients’ ability to carry out high dose of massed practice.